1987
DOI: 10.1017/s0007485300011731
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of the maize stalk borer, Busseola fusca (Fuller) (Lepidoptera: Noctuidae)

Abstract: New information on the intraseasonal progression of larval infestations of Busseola fusca (Fuller) in South Africa was obtained through repeated sampling in maize plantings of different planting dates over various seasons. Due to the occurrence of distinct periods of moth flight, variation in planting date had a marked influence on levels of larval infestation. Also, plants were found to be most attractive as sites for oviposition between three and five weeks after emergence, resulting in a definite pattern in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 13 publications
3
67
2
Order By: Relevance
“…Tydskr. Plant Grond 1996, 13(3) emergence, which represents the peak occurrence of oviposition in the field (van Rensburg et at., 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Tydskr. Plant Grond 1996, 13(3) emergence, which represents the peak occurrence of oviposition in the field (van Rensburg et at., 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Knutson and Gilstrap, 1990, Trichilo and Leigh, 1985, Mansour and Karchi, 1990, Zabudskaya, 1990and van Rensburg and Malan, 1990. In the studies presented in chapters 2 and 3 the distinction was made and it was found that the number of non-laying females increased, as the suitability of the plants to which the females were exposed to decreased.…”
Section: Preference -Performance Relationships In the Glasshouse Whitmentioning
confidence: 99%
“…The importance of this stalk borer has also been reported in eastern and southern Africa (Dabrowski, 1985), as well as in Nigeria (Harris, 1962). Owing to the importance of B. fusca as a limiting factor to maize production on the African continent, its biology, ecology and control have been extensively investigated elsewhere in Africa (Mally, 1920;du Plessis & Lea, 1943;Harris, 1962;Usua, 1968;Walters et al, 1976;van Rensburg, van Rensburg & Malan, 1980;van Rensburg, Walters & Giliomee, 1985, 1987, 1988a. Although B.fusca has also been reported to attack maize in Lesotho (Qhobela et al, 1986), no further s~udy was conducted on the pest.…”
Section: Introductionmentioning
confidence: 99%
“…The tiille of planting was reported to have a pronounced effect on the levels of infestation and subsequent yield loss caused by stalk borers in maize (Swaine, 1957;Harris, 1962;Abu, 1986;van Rensburg et at., 1985van Rensburg et at., , 1987Gebre-Amlak, Sigvald & Petterson, 1989). This phenomenon has been attributed to the occurrence of distinct periods of moth flight (van Rensburg et al, 1987).…”
Section: Introductionmentioning
confidence: 99%